Analisis Hukum Peran Kejaksaan dalam Penuntutan Tindak Pidana Korupsi (Studi Kasus di Kejaksaan Negeri Tebing Tinggi). - Tarigan, Edi Syahjuri; Marlina, Marlina; Siregar, Taufik (Universitas Medan Area, 2020)
This article discusses several issues, namely: how the legal position of the prosecutor's office in prosecuting criminal acts of corruption; how is the implementation of the position and role of the prosecutor in prosecuting criminal acts of corruption; and how to overcome obstacles in carrying out prosecutions of corruption. The research method used is the normative legal method, which analyzes and seeks answers to issues raised based on the substance of the law / legal norms contained in legislation, the Attorney General's Regulation, the Attorney General's Circular, and others. The results showed that the role of prosecutors in controlling criminal and non-criminal acts of corruption has not been maximized because there are obstacles in the implementation of their duties and authorities from both internal and external factors. In carrying out this task, the Attorney General's Office always strives to improve the quality of the management of tasks assigned to it, one of which is in handling corruption cases. Corruption practices that tend to increase are a serious matter for efforts to deal with law in Indonesia, especially the Attorney General's Office.Â